Exploring the Nexus Between CSR, Governance, and Financial Performance in Islamic Firms: Review of Their Financial Implications - Al Bahri, Abil Arqom; Faisal, Yudi Ahmad (PT FORMOSA CENDEKIA GLOBAL, 2025)
The relationship between Corporate Social Responsibility (CSR), Good Corporate Governance (GCG), and financial performance in Islamic firms has been widely studied. While CSR and GCG enhance transparency, risk mitigation, and investor confidence, their direct impact on profitability remains debated. This systematic literature review (SLR) analyzes 32 empirical studies on CSR and GCG in Islamic banking and financial institutions. Findings show that strong governance, ethical business practices, and strategic CSR initiatives support long-term financial resilience, particularly in well-regulated Islamic banks. However, challenges like reporting inconsistencies, regulatory disparities, and compliance costs create performance variations across jurisdictions. The study emphasizes the need for standardized Islamic Social Reporting (ISR) frameworks and regulatory harmonization across Islamic financial markets to improve comparability. Future research should develop integrated models that balance financial sustainability with Shariah compliance, ensuring optimized governance without compromising profitability.